Lean production em pequenas e médias empresas: análise dos desafios na implantação em processadoras de amendoim - Medeiros, Ronaldo Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
The peanut value chain plays a significant role in São Paulo’s agroindustry, and the Alta Paulista region is home to small and medium-sized enterprises (SMEs) engaged in processing activities and in the generation of economic and social value. Although lean production is often identified as a pathway to efficiency gains, its implementation in SMEs in this sector tends to occur unevenly, with isolated advances and difficulties in consolidating practices into routines. This dissertation investigated the implementation of lean in peanut-processing SMEs in Alta Paulista based on three analytical dimensions: culture of implementation (Culture of Implementation of Lean Philosophy – CIFL), adoption and execution of practices and tools (Assessment of Lean Tools and Formalization Level – AVFL), and overcoming implementation challenges (Superation of Difficulties in Lean Implementation – SDIL). The study combined a systematic literature review and content analysis, which made it possible to organize and consolidate variables related to implementation barriers. Subsequently, an explanatory survey was conducted with managers in the sector using a structured Likert-scale instrument. To address the uncertainty inherent in the assessments and obtain a comparable classification across companies, the data were analyzed using the multicriteria Fuzzy TOPSIS-CLASS method, generating class-based profiles for the three constructs. The results show a predominance of a culture favorable to lean, coexisting with low formalization in the adoption of tools and standards, as well as persistent challenges at moderate to high levels. The integrated reading indicates a mismatch between cultural orientation and systematic execution: initiatives emerge, but they do not always become stabilized in routines, indicators, and monitoring mechanisms. It is concluded that, for agroindustrial SMEs, progress in lean depends on continuous training, leadership capable of deploying objectives and enforcing routine accountability, context-compatible standardization, and simple monitoring governance, in order to reduce the gap between intention and practice.

A cadeia do amendoim tem peso relevante na agroindústria paulista, e a região da Alta Paulista abriga pequenas e médias empresas (PMEs) com atuação no processamento e na geração de valor econômico e social. Embora o lean production seja frequentemente apontado como caminho para ganhos de eficiência, sua implantação em PMEs do setor tende a ocorrer de modo heterogêneo, com avanços pontuais e dificuldades de consolidação em rotinas. Esta dissertação investigou a implementação do lean em PMEs processadoras de amendoim da Alta Paulista a partir de três dimensões analíticas: cultura de implantação (Culture of Implementation of Lean Philosophy – CIFL), adoção e execução de práticas e ferramentas (Assessment of Lean Tools and Formalization Level – AVFL) e superação de desafios na implantação (Superation of Difficulties in Lean Implementation – SDIL). O estudo combinou revisão sistemática da literatura e análise de conteúdo, que permitiram organizar e consolidar variáveis relacionadas às barreiras de implementação. Posteriormente, foi aplicado um survey explanatório com gestores do setor, por meio de instrumento estruturado em escala Likert. Para tratar a incerteza inerente às avaliações e obter uma classificação comparável entre as empresas, os dados foram analisados pelo método multicritério fuzzy TOPSIS-CLASS, com geração de perfis por classe para os três construtos. Os resultados mostram predominância de cultura favorável ao lean, coexistindo com baixa formalização na adoção de ferramentas e padrões, além de desafios persistentes em nível moderado a elevado. A leitura integrada indica um descompasso entre orientação cultural e execução sistemática: iniciativas aparecem, mas nem sempre se estabilizam em rotinas, indicadores e mecanismos de acompanhamento. Conclui-se que, para PMEs agroindustriais, o avanço do lean depende de capacitação continuada, liderança com desdobramento e cobrança de rotina, padronização compatível com o contexto e governança simples de acompanhamento, de modo a reduzir a distância entre intenção e prática.
Lean production in small and medium-sized enterprises: analysis of the challenges of implementation in peanut processing companies
Keywords: Produção enxuta; Pequenas e médias empresas; Processamento de amendoim; Agronegócio; Eficiência operacional; Implementação lean; Lean production; Small and medium-sized enterprises; Peanut processing; Agribusiness; Operational efficiency; Lean implementation